ANALISIS PERBEDAAN LAPORAN KEUANGAN KONVENSIONAL DAN SYARIAH - Dewi Rahma Fauziah; Refi Refalia (STAI La Tansa Mashiro, 2024)
Financial statements (Financial Statement) are the end product of the process of Recording and summarizing business transaction data, an accountant is expected to be able to Manage all accounting data so as to produce financial reports and even have to be able to Interpret and analyze the financial reports he makes. The benchmark for whether or not a Financial institution or company is healthy is seen from the financial statements and this will Affect the decisions of external parties in terms of investment or otherwise. Many things. In Essence, the purpose of both is the same, namely to present reports from health institutions or Prushan in the form of financial statements. Keywords : Financial Statements, Conventional Banks, Sharia Banks, Financial Analysis